CD39 is an antibody-secreting B-cell marker that modulates germinal center and antibody responses during infection - Almada, Laura; Gazzoni, Yamila N.; Beccaria, Cristian G.; Fiocca Vernengo, Facundo; Boccardo, Santiago; Gorosito Serrán, Melisa; Trivedi, Apurwa; Vinuesa, Carola G.; Robson, Simon C.; Acosta Rodríguez, Eva V.; Gaya, Mauro; Montes, Carolina L.; et al. (Frontiers in Immunology, 2025)
CD39 is an ectoenzyme in immune cells that regulates purinergic signaling by converting extracellular ATP into adenosine (ADO). Although first described on EBV-transformed B cells, CD39’s role in humoral immunity remains unclear. Using murine infection models and human samples, we confirm and extend previous findings showing that high CD39 expression identifies antibody-secreting cells (ASC) across differentiation stages, including ASC derived from memory B cells, and in various tissues, regardless of the infection phase. CD39 was resistant to enzymatic digestion, facilitating ASC identification in processed tissues. We found that while CD39 was not essential for B-cell differentiation into ASC, it remained functionally active as an ectoenzyme. ASC as well as germinal center (GC) B cells expressed ADO receptors, making them responsive to ADO signaling. Consistently, systemic ADO administration impaired GC reactions without altering the ASC number in infected mice. However, in vitro, ADO reduces antibody production both in ASC and in B cells undergoing differentiation and also impairs the differentiation of activated B cells. Finally, B cell–specific CD39 deficiency increased GC B-cell frequencies in infected mice, likely due to reduced ADO levels. These findings highlight the relevance of the purinergic pathway in B-cell biology.